2017
DOI: 10.1016/j.tate.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and personalisation in teacher education; the case of blogging

Abstract: Through narrative analysis, we find the process of blogging noteworthy in lending itself to pre-service teachers' professional learning in at least two significant ways. Firstly, blogging can open the potential for collaboration through the discursive space that exists for student teachers as they negotiate the demands placed upon them from school-based and University-based elements of their course. Secondly, blogging appears compatible with a narrative conception of professional learning in which pre-service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Also, using the framework for understanding teaching and learning (Bransford, Darling-Hammond, et al, 2005) as part of question two helped me examine how participants were or were not making connections between theory and practice and understand the types of discussions happening among teachers in this online space. Additionally, while it is known that teachers engage in online learning spaces, it is not yet known how these spaces influence their work in classrooms (Kelly & Antonio, 2016;Killeavy & Moloney, 2010;Macià & García, 2016;Turvey & Hayler, 2017). This study helped to examine how discussions in an online space can inform teaching practices in the classroom…”
Section: Chapter Iii: Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…Also, using the framework for understanding teaching and learning (Bransford, Darling-Hammond, et al, 2005) as part of question two helped me examine how participants were or were not making connections between theory and practice and understand the types of discussions happening among teachers in this online space. Additionally, while it is known that teachers engage in online learning spaces, it is not yet known how these spaces influence their work in classrooms (Kelly & Antonio, 2016;Killeavy & Moloney, 2010;Macià & García, 2016;Turvey & Hayler, 2017). This study helped to examine how discussions in an online space can inform teaching practices in the classroom…”
Section: Chapter Iii: Methodologymentioning
confidence: 99%
“…The following research questions guided my study as I sought to understand the potential of an online thirdspace where preservice and in-service teachers could engage in critical reflections and discussions. The questions that I crafted for this study potentially add to the field of education because previous literature has suggested a need to study small closed social networking sites (Kelly & Antonio, 2016;Killeavy & Moloney, 2010;Macià & García, 2016;Turvey & Hayler, 2017) and thirdspace theory has suggested a need to study a place where connections and disconnections between two spaces can be explored for reflection and renewal (Flessner, 2014). Also using the framework for understanding teaching and learning (Bransford, Darling-Hammond, et al, 2005) as a guiding question has helped me examine how participants are or are not making connections between theory and practice and understand what is happening in online spaces among educators.…”
Section: Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations